2002
DOI: 10.1046/j.1464-410x.2002.02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaginal distension on urethral anatomy and function

Abstract: Objective  To determine the effect of repeated and prolonged vaginal distension on the leak‐point pressure (LPP) and urethral anatomy in the female rat, as prolonged vaginal distension has been clinically correlated with signs of stress urinary incontinence (SUI). Materials and methods  Sixty female rats were placed into one of five groups; four groups underwent one of four vaginal distension protocols using a modified 10 F Foley catheter, i.e. prolonged (1 h), brief (0.5 h), intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
4
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(181 citation statements)
references
References 26 publications
(32 reference statements)
6
168
4
3
Order By: Relevance
“…In addition, they have previously reported that a lesser duration of VD or intermittent cycling VD does not result in changes in urethral resistance. 24 Active middle urethra sneeze induced reflex responses are present but decreased by approximately 50% after simulated childbirth injury (VD) in rats. 26 However, they were increased by intravenous nisoxetine and decreased by intrathecal phentolamine and prazosin, suggesting that this injury simulates clinical SUI and it may be treatable with a norepinephrine reuptake inhibitor.…”
Section: Models Simulating Maternal Childbirth Injuriesmentioning
confidence: 99%
“…In addition, they have previously reported that a lesser duration of VD or intermittent cycling VD does not result in changes in urethral resistance. 24 Active middle urethra sneeze induced reflex responses are present but decreased by approximately 50% after simulated childbirth injury (VD) in rats. 26 However, they were increased by intravenous nisoxetine and decreased by intrathecal phentolamine and prazosin, suggesting that this injury simulates clinical SUI and it may be treatable with a norepinephrine reuptake inhibitor.…”
Section: Models Simulating Maternal Childbirth Injuriesmentioning
confidence: 99%
“…Apresentam-se na Tabela Entre os fatores que podem estar associados à incontinência urinária por esforço é a deficiência esfincteriana uretral intrínseca, aumento da pressão intraabdominal, período gestacional, elevado número de partos, trauma obstétrico, obesidade, tabagismo, doenças neurológicas, doenças respiratórias crônicas e tratamentos cirúrgicos ginecológicos (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . A mulher incontinente, principalmente as casadas ou com vida sexual ativa, sofrem grande impacto na sua qualidade de vida, porque estão sempre com medo ou com receio de perder urina em certas situações como durante a relação sexual, quando sentem receio de As infecções urinárias de repetição provocam a urgeincontinência (3) .…”
Section: Resultsunclassified
“…Ainda, alterações anatômicas podem provocar a IU como a hipermobilidade da uretra e deficiência esfincteriana (3,14) , modificações do assoalho pélvico (15) , distensões nas fibras musculares da uretra (7) e instabilidade do músculo detrusor da bexiga urinária (4,16) .…”
Section: Introductionunclassified
“…A similar distention protocol was used as above, except 400 l of saline was injected in the balloon due to the animals' smaller size. The previously validated Mouse Pelvic Organ Quantification (MOPQ) exam was used to measure the degree of vaginal, perineal, and anal prolapse in all animals preoperatively and then on postoperative days 3,6,10,14, and continued weekly until postoperative day 98 (i.e., 14 wk after the distention, or 20 wk of age). The MOPQ was completed by having one investigator hold the animal by the scruff of the neck, which resulted in a prolonged, reflex valsalva (evidenced by defecation), while the other investigator performed the measurements using a caliper with the precision of 1/100th of a millimeter.…”
Section: Methodsmentioning
confidence: 99%